Dynamic Hardware Development. (21st September 2008) - Craven, Stephen; Athanas, Peter
Abstract : Applications that leverage the dynamic partial reconfigurability of modern FPGAs are few, owing in large part to the lack of suitable tools and techniques to create them. While the trend in digital design is towards higher levels of design abstractions, forgoing hardware description languages in some cases for high-level languages, the development of a reconfigurable design requires developers to work at a low level and contend with many poorly documented architecture-specific aspects. This paper discusses the creation of a high-level development environment for reconfigurable designs that leverage an existing high-level synthesis tool to enable the design, simulation, and implementation of dynamically reconfigurable hardware solely from a specification written in C. Unlike previous attempts, this approach encompasses the entirety of design and implementation, enables self-re-configuration through an embedded controller, and inherently handles partial reconfiguration. Benchmarking numbers are provided, which validate the productivity enhancements this approach provides.